Influence of the structural features of commercial mannoproteins in white wine protein stabilization and chemical and sensory properties - Ribeiro, Tânia Isabel Monteiro (2014)
The cloudy aspect formed in white wines due to protein instability is a visual defect. Sodium bentonite is the most commonly used fining agent to treat this instability, but has usually a negative impact on the wine’s physicochemical and sensory characteristics. Aiming to find suitable alternatives, eleven commercial mannoproteins were chemically characterized concerning their sugar composition and protein content, and their effectiveness on wine protein stabilization. Also, their effect on the amount and nature of phenolic compounds, browning potential, chromatic and sensory characteristic was evaluated. Protein stabilization effectiveness was related to their chemical composition, namely their high mannose to glucose ratio. Additionally, some mannoproteins decreased the browning potential. Thus, mannoproteins could be an effective alternative for protein stabilization, preserving or even improving wine quality.